Extraction and Application of Secondary Metabolites from Parmelia perlata - K, Leela; Iyer, Priya (Asian Journal of Biological and Life Sciences, 2016)
Parmelia perlata is a lichen that is a symbiotic association between fungi and algae belonging to the family Parmeliaceae. It is also consumed as an edible source in India.The present study was focussed on extracting and evaluating the application of secondary metabolites from the lichen sample. The sample was extracted using methanol as solvent by cold extraction method and phytochemical analysis was carried out to determine the presence of secondary metabolites. The antibacterial activity of lichen Parmelia perlata was tested against 2 gram (+) ve bacteria Staphylococcus aureus, Bacillus subtilis and 2 gram (-) ve bacteria Pseudomonas aeruginosa and Escherichia coli. Anticancer activity was determined against MCF-7 breast cancer cell lines using MTT assay where the sample showed a rapid decrease in the percentage of cell viability. The antioxidant activity was also determined by DPPH assay, TCA assay and H2O2 assay.The sample was purified by means of column chromatography and the purified sample was estimated by Gc-Ms analysis to reveal the presence of major secondary compounds. The dye yielding potential of lichen Parmelia perlata was also assessed by boiling water method (BWM) and di-methyl sulphoxide extraction method (DEM) .The extracted dyes were tested onto fabrics with and without the use of mordants and the anticancer activity of the dye obtained by BWM method wasalso assessed in order to test its efficacy as a potential food colorant.
Keywords: Antibacterial activity; Anticancer activity; Antioxidant activity; Column chromatography; Dye; Gc-Ms analysis; Parmelia perlata; Secondary metabolites